Women in Accounting Information Systems Research: An Account from Self-Reflection - Wong, E.S.K. (Universiti Putra Malaysia, 2009)
Very little evidence exists to explain why only a few women have undertaken career as academic researcher in information systems. John Lucas (1973) suggests that the feminist debate may lead to the application of certain concepts of justice, equality, and humanity. This being so, a central question for this paper is “Why is the academic management industry far from being gender neutral?” The author perceives that society as it stands, is still unfair to women, and that this unfairness should be addressed. This paper also deals with and brings up unanswered questions as to whether discrimination against suitably qualified women for such positions could ever be defended according to the current principles of social justice. On the other hand, there are explanations of the phenomena premise on Maccoby’s (1998) findings on same sex aggregation, and the latest research of Robert Munroe and Kimball Romney indicate (2006) that Maccoby’s findings are not challenged by cross-cultural results. Hence, the same sex preference is a universal phenomenon.